Meningkatkan Hasil Belajar Pendidikan Agama Katolik Melalui Media Gambar Pada Siswa Kelas III SD YPPK Santa Maria Fatima Kelapa Lima Merauke - Pranyoto, Yohanes Hendro; Tonggon, Edmunda O. (Jurnal Masalah Pastoral, 2024)
This study aims to determine the effectiveness of using picture media as learning media to improve student learning outcomes. This research is a classroom action research (PTK) conducted in 2 (two) cycles with team teaching. The research location was at SD YPPK Santa Maria Fatima Kelapa Lima Merauke with class III students as many as 24 people. Research data were collected using observation sheets, test instruments, and student worksheets. The results showed that students' ability in KD 1 in the pre-cycle period was indicated by the class average score of 65, which increased in cycle I and cycle II to 69 and 70. The percentage of students who reached the KKM for KD 1 also showed an increase. In the pre-cycle period, 50% increased at the end of cycles I and II by 70.8% and 83%. In addition, the results of observations of student activity in the classroom also showed an increase in student learning participation in the classroom, namely in cycle I as many as 16 students and cycle II as many as 20 students. Based on these data, it can be concluded that the use of image media can improve student learning outcomes. Based on this research, the author recommends the use of learning media that uses visual and auditory approaches for small class students such as grades I, II and III in elementary school.